Защитные бронзовые гальванопокрытия: перспективы использования для повышения надежности и сроков эксплуатации аварийно-спасательной техники.2. Изучение микроструктуры и свойств покрытий - Reva Ольга; Mikhalyuk Сергей; Bogdanova Валентина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The research has been carried out of the dependence microstructure, physical and mechanical properties of the bronze coverings, synthesized by electrochemical sedimentation from solutions, on their phase and chemical composition. Advantage of electrochemical alloys over metallurgical analogues has been shown at their use for protection details of the rescue mechanics, maintained in any weather conditions and excited environments, against corrosion and mechanical deterioration. The reasons of not trivial physical and mechanical properties the galvanic alloys are established, and prospects of their application for increasing the saving mechanisms and motor-vehicles reliability and terms of operation have been proved.